CGIAR AI landscape 2025: Needs, opportunities, and next steps - CGIAR Accelerator on Digital Transformation; Jones-Garcia, Eliot; Martins, Carolina; Magalhaes, Marilia; Koo, Jawoo (CGIAR System Organization, 2025)
Transforming food, land, and water systems (FLWS) in a climate crisis requires scientific collaboration at a scale and speed that traditional research infrastructures can no longer support. CGIAR’s 2030 Research and Innovation Strategy recognizes this urgency and positions the digital revolution as a core enabler of systemwide change. The Digital Transformation Accelerator (DTA) is committed to operationalizing this vision: reducing fragmentation, enabling cross-Center collaboration, and providing the connective tissue that links CGIAR’s science with workflows that are interdisciplinary, scalable, and impact-ready. Key focus areas are shown in box 1.